Revolution in Eastern Europe : understanding the collapse of communism in Poland, Hungary, East Germany, Czechoslovakia, Romania, and the Soviet Union - Cipkowski, Peter (Our changing world series, 1991)
Written by an expert in European studies for young adults. Explains and analyzes the fall of communism in Eastern Europe. Scores of photographs, political cartoons and maps make this book visually appealing. Country by country, the author covers the enormous changes that occurred throughout the Fall of 1989 as well as events in the nine months that followed.